Development of a Stability Index for Evaluating Drivers’ Psychological Stability During Truck Platooning - Cho, Hyonbae; Kim, Yejin; Oh, Seok Jin; Yun, Ilsoo (Applied Sciences (Switzerland), 2025)
This study proposes a stability index to quantitatively evaluate the psychological stability of drivers during truck platooning. Truck platooning is a technique in which a manually driven lead truck is followed by automated trucks using V2X communication and onboard sensors. While significant technical advances have been made in truck platooning, research on drivers’ psychological comfort remains limited. Due to the shorter intervehicle time gaps compared to conventional trucking, truck platooning raises concerns regarding drivers’ psychological stability. The proposed index quantifies this aspect and is validated using a driving simulator. Both the stability index calculations and the survey consistently indicate that when the time gap decreases to 0.6 s (approximately 15 m) or less, drivers’ psychological stability deteriorates. However, increasing the time gap beyond 0.6 s does not significantly improve it. Furthermore, this study investigates the effect of the see-through functionality, which provides real-time front-view footage of the preceding vehicle to the following driver. The results confirm that this functionality enhances psychological stability, even under a short time gap. The stability index should serve as a practical indicator for designing truck platooning systems that consider drivers’ psychological stability and may be extended to various advanced driving technologies, including general vehicle platooning.
Keywords: A-stability; Automated trucks; Driving simulator; Intervehicle time gap; On-board sensors; Psychological stability; See-through functionality; Stability indices; Time gap; Truck platooning; driving simulator; intervehicle time gap; psychological stability; see-through functionality; stability index; truck platooning